Social Enterprises like the Right Step for Economic Development for Kosovo (European Journal of Marketing and Economics, 2018)
Over the last few years, social enterprises have created a new social and developmental concept with a rapid growth seen by Kosovar society as a new form of doing business, but rather well organized and contributing to economic and social development, as one of the most fair forms for society in equitable capital use that provides opportunities to all individuals, groups and communities regardless of their needs and capabilities. How we should conceptualize social enterprises, they are enterprises that combine social purpose with the spirit of the entrepreneur. Social enterprises are enterprises that provide profits, but entrepreneurs make this profit and re-invest in products and services they provide to achieve a wider social impact in the community they serve and act. The activity of social enterprises is diverse, contributing to the social inclusion of the marginalized groups of the society in order to increase employment and increase the incomes. Therefore in Kosovo, the development of social enterprises is still in its initial stage of development. The first social enterprises have started their activities recently with the help of donor organizations. In the absence of a law on social enterprises, they operate with a non-profit, less lucrative status. For the promotion and creation of social enterprises, especially at this stage, we aim at sustainable economic and social development, where as part of this it can play the role of supplier in the in Kosovos internal market. The purpose of this paper is to shape the theories and best practices of social enterprises as one of the main goals of development and creation of a better economic environment for the disadvantaged society for employment in these social enterprises. In Kosovo, as in many countries in Southeast Europe, there is an increase in the involvement of non-profit organizations in economic activities, which aim at integrating disabled persons as well as providing services to the benefit of society.
Keywords: Social Enterprises, Economic Development, Market, Employment, Kosovo